Prescribing Pattern and Drug Use in Ophthalmology Out Patient Department of Nepalgunj Medical College, Nepalgunj, Nepal - Dhami, Dabal Bahadur; Thapa, Bikram B; Neupane, Ganesh Prasad (Journal of Nepalgunj Medical College, 2017)
Introduction: Monitoring, evaluation and modification of prescriptions of prescriber can be achieved by the study of prescribing pattern through prescription audit. WHO and INRUD have evolved standard drug use indicators to improve the overall drug use in developing nations like Nepal. Aims and objective: To describe the patterns of prescription and drug use at ophthalmology at outpatient department (OPD). Materials and methods: The study was conducted at Out Patient Department of ophthalmology at Nepalgunj Medical College, Nepalgunj. The data was collected from the patients who visited the OPD during the period from May to November 2017. Total 855 Prescriptions were audited and WHO drug prescribing and use indicators were analyzed. Results: The number of drugs per prescription varied from one to five with an average of 2.6. Majority of drug 97% was prescribed in brand name. The maximum (76%) drugs were prescribed as topical form. Eye drops 64% were the most commonly prescribed followed by ointments (12%), tablets (11%), capsules (9%), syrups (3%) and injections (1%). Sixty percent lubricants were prescribed followed by anti-allergic and Anti-inflammatory (20%) then antimicrobials 17%, Mydriatric and cycloplegic 7%. The dosage forms of the drugs were recorded for 92% and the frequency of administration was recorded for 96% of the prescriptions whereas duration of treatment was mentioned for 66% of the prescription. Conclusion : In the hospital setting drug utilization pattern must be monitored time to time to analyze their rational use, provide feedback and suggestion to the prescriber.